A new contribution to Megasporoporia sensu lato: Six new species and three new combinations - Ya-Rong Wang; Yu-Cheng Dai; Hong-Gao Liu; Josef Vlasák; Peter Buchanan; Yuan Yuan; Ying-Da Wu; Ying-Da Wu (Frontiers in Microbiology, 2022)
Megasporoporia sensu lato has recently been intensively studied in China and South America, and four independent clades representing four genera have been recognized phylogenetically. In this study, more samples, mostly from subtropical and tropical Asia, Oceania, and East Africa, are analyzed. A phylogeny based on a 4-gene dataset of sequences (ITS + nLSU + mtSSU + tef) has confirmed the presence of four genera in Megasporoporia sensu lato: Jorgewrightia, Mariorajchenbergia, Megasporia, and Megasporoporia sensu stricto. Six new species, Jorgewrightia austroasiana, Jorgewrightia irregularis, Jorgewrightia tenuis, Mariorajchenbergia subleucoplaca, Megasporia olivacea, and Megasporia sinuosa, are described based on morphology and phylogenetic analysis. Three new combinations are proposed, viz. Jorgewrightia kirkii, Mariorajchenbergia epitephra, and Mariorajchenbergia leucoplaca. To date, 36 species of Megasporoporia sensu lato are accepted and an identification key to these species is provided. In addition, the identification of Dichomitus amazonicus, Dichomitus cylindrosporus, and Megasporoporia hexagonoides is discussed.